Converting pseudocodes into Python functions (Operations on data structures and trees) - Chua, Derek Cheng Jun (Nanyang Technological University, 2024)
Data structure is the means of organizing data into the computer’s memory so it can be used conveniently and efficiently, different basic and advance types of data structures represented in stacks, queues, linked lists and tree traversals. This subject is taught to students in ‘IE2108 Data Structure and Algorithms in Python’ to introduce data structures and algorithms for constructing efficient computer programs and studies the principles of algorithmic analysis. Most students mainly learn about the different data structures and algorithms for academic purposes without fully understanding them. By showcasing the learnt algorithms in real-world applications, it can help students improve their comprehension for the subject by using the applications and seeing how the algorithm operates. This guarantees that the content learnt is understood as an invaluable asset.